The energy consumption and economic growth nexus in China - Umihidayah, binti Besar (Universiti Malaysia Sarawak (UNIMAS), 2015)
The purpose of this study is to examine the relationship between energy consumption and economic growth in China. This study uses time series data of hydroelectricity, coal and oil energy consumption and economic growth measured by gross domestic product (GDP) in China. The Data ranges from 1976 to 2013. It is collected from World Data Bank and BP Statistical Review of World Energy. The findings show that coal consumption and oil consumption have a long run causality towards the hydroelectricity consumption and nominal gross domestic product. Nowadays, the energy sector is one of the largest contributor to the harmful environmental problem in China. Thus, the policy makers should be aware of this problem and implement policy that may reduce the environment problem especially on the pollution.